The dimensions of equality in a Roma Student College - Varga, Aranka (Autonomy and Responsibility Journal of Educational Sciences, 2022)
The aim of this study is to present social philosophy and social political approaches that are also crucial for education. The examination of dimensions of equality and its psychological and pedagogical approaches, may contribute to the effi cient, effective and equitable operation of a diverse student environment. Furthermore, connecting the concept of inter-sectionalism, empowerment, the inclusive student environment, and the characteristics of a resilient student features a pedagogical perspective of sociological and social political questions. In support of the conceptual “adaptation”, the professional concept of Wlislocki Henrik Student College at University of Pécs was utilized, and life path interviews with the college students were analysed as an example. By this approach we can simultaniously learn about the Roma Student College based on its own principles and practice, and we can look at the issue of equality along the contextual system of the related conceptual dimensions.